Phosphopeptide Screen Uncovers Novel Phosphorylation Sites of Nedd4-2 That Potentiate Its Inhibition of the Epithelial Na+ Channel - Hallows, Kenneth R.; Bhalla, Vivek; Oyster, Nicholas M.; Wijngaarden, Marjolein A.; Lee, Jeffrey K.; Li, Hui; Chandran, Sindhu; Xia, Xiaoyu; Huang, Zhirong; Chalkley, Robert J.; Burlingame, Alma L.; Pearce, David (The Journal of biological chemistry, 2010)
The E3 ubiquitin ligase Nedd4-2 regulates several ion transport proteins, including the epithelial Na+ channel (ENaC). Nedd4-2 decreases apical membrane expression and activity of ENaC. Although it is subject to tight hormonal control, the mechanistic basis of Nedd4-2 regulation remains poorly understood. To characterize regulatory inputs to Nedd4-2 function, we screened for novel sites of Nedd4-2 phosphorylation using tandem mass spectrometry. Three of seven identified Xenopus Nedd4-2 Ser/Thr phosphorylation sites corresponded to previously identified target sites for SGK1, whereas four were novel, including Ser-293, which matched the consensus for a MAPK target sequence. Further in vitro and in vivo phosphorylation experiments revealed that Nedd4-2 serves as a target of JNK1, but not of p38 MAPK or ERK1/2. Additional rounds of tandem mass spectrometry identified two other phosphorylated residues within Nedd4-2, including Thr-899, which is present within the catalytic domain. Nedd4-2 with mutations at these sites had markedly inhibited JNK1-dependent phosphorylation, virtually no ENaC inhibitory activity, and significantly reduced ubiquitin ligase activity. These data identify phosphorylatable residues that activate Nedd4-2 and may work together with residues targeted by inhibitory kinases (e.g. SGK1 and protein kinase A) to govern Nedd4-2 regulation of epithelial ion transport.